Association between measures of kidney function and preserved ratio impaired spirometry in diabetes: NHANES 2007–2012 - Hui Xu; Coen D A Stehouwer; Jin-Yan Zhang; Ikramulhaq Patel; Hong-Jian Gong; Yin-He Chai; Yu-Shun Qiao; Meng-Ting Zhang; Jianbo Zhou (BMJ Open)
Objectives This study aimed to examine the relationship between measures of kidney function and impaired lung function in individuals with diabetes and to assess all-cause mortality risk associated with having chronic kidney disease (CKD) and or impaired lung function.Design Cross-sectional and retrospective cohort study.Setting The National Health and Nutrition Examination Survey 2007–2012.Participants A total of 10 809 participants aged over 20 years were included in this study: 9503 with normal spirometry, 951 with preserved ratio impaired spirometry (PRISm) and 355 with variable obstruction (VO).Exposure and outcome measures Kidney function measures, including estimated glomerular filtration rate (eGFR) and urinary albumin to creatinine ratio (UACR), were considered exposure variables. PRISm and VO were outcome variables. PRISm was defined as a forced expiratory volume in 1 s (FEV1)<80% predicted and an FEV1/forced vital capacity (FVC) ratio≥0.7, while VO was defined as an FEV1/FVC ratio <0.7 prebronchodilator and ≥0.7 postbronchodilator. In the cross-sectional analysis, multivariate logistic regression models were used to assess the relationship between kidney function measures and spirometry findings. In the retrospective cohort analysis, Cox proportional hazards models were employed to evaluate the impact of having PRISm or VO, combined with CKD, on all-cause mortality.Results An increase in UACR was significantly associated with higher odds of PRISm (OR (95% CI)=1.10 (1.01, 1.21), p=0.03). Additionally, eGFR <60 was associated with the odds of variable obstructive lung function (OR (95% CI)=1.72 (1.07, 2.74), p=0.03) compared with eGFR >60. After adjustments, an increase in UACR was associated with higher odds of PRISm in individuals with diabetes (OR (95% CI)=1.21 (1.08, 1.36), p=0.002), and UACR ≥300 mg/g significantly increased odds of having PRISm in idividuals with diabetes (OR (95% CI)=2.34 (1.23, 4.47), p=0.01). During a mean follow-up of 12.3 years, 10 500 deaths occurred. In the diabetic group, compared with normal spirometry without CKD, those with both PRISm and CKD had a significantly increased risk of all-cause mortality (HR (95% CI)=3.46 (1.94, 6.16), p<0.0001).Conclusion An elevated UACR and albuminuria were linked to a higher risk of PRISm. Our study emphasises that kidney and lung function are correlated. Further research is necessary to confirm our findings.